2009
DOI: 10.3892/mmr_00000107
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of catenin subtypes is a potential indicator of unfavorable prognosis in esophageal squamous cell carcinoma

Abstract: Abstract. Catenins are cytoplasmic proteins that play a pivotal role in cell adhesion. Conflicting results regarding the significance of their expression in esophageal squamous cell carcinoma (ESCC) have been reported. The expression of ·-, ß-and Á-catenin was examined using immunohistochemical methods in 69 samples collected from patients with ESCC who were surgically treated without any preoperative induction therapy. Reduced ·-, ß-and Á-catenin expression was observed in 48 (69.7%), 36 (52.2%) and 44 (63.8%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…However, plakoglobin may function as a tumor/metastasis suppressor independent of its adhesive function by modulating Rho, Fibronectin and vitronectin-dependent Src signaling (Todorović et al, 2010;Franzen et al, 2012), by acting as a transcriptional repressor of oncogenic Myc (Williamson et al, 2006) and by increasing the expression of metastasis suppressors such as Nm23 (Aktary et al, 2010) and 14-3-3s. These in vitro observations are supported by clinical studies that have shown decreased plakoglobin expression leads to tumorigenesis, increased risk of metastasis and poor overall prognosis in various tumors (Pantel et al, 1998;Kanazawa et al, 2008;Närkiö-Mäkelä et al, 2009;Nozoe et al, 2009;Aktary and Pasdar, 2012;Holen et al, 2012).…”
Section: Discussionsupporting
confidence: 58%
“…However, plakoglobin may function as a tumor/metastasis suppressor independent of its adhesive function by modulating Rho, Fibronectin and vitronectin-dependent Src signaling (Todorović et al, 2010;Franzen et al, 2012), by acting as a transcriptional repressor of oncogenic Myc (Williamson et al, 2006) and by increasing the expression of metastasis suppressors such as Nm23 (Aktary et al, 2010) and 14-3-3s. These in vitro observations are supported by clinical studies that have shown decreased plakoglobin expression leads to tumorigenesis, increased risk of metastasis and poor overall prognosis in various tumors (Pantel et al, 1998;Kanazawa et al, 2008;Närkiö-Mäkelä et al, 2009;Nozoe et al, 2009;Aktary and Pasdar, 2012;Holen et al, 2012).…”
Section: Discussionsupporting
confidence: 58%
“…Li et al, 2009;Nozoe et al, 2009;Situ et al, 2010;Chen et al, 2011;Wang et al, 2011;Lv et al, 2012) investigating the correlation between β-catenin expression and the OS of EC patients were included in the metaanalysis, of which nine studies (Shiozaki et al, 2000;Hsu et al, 2008;Lin et al, 2008;Li et al, 2009;Nozoe et al, 2009;Situ et al, 2010;Chen et al, 2011;Wang et al, 2011;Lv et al, 2012) investigated Asian patients, and one (Krishnadath et al, 1997) investigated European patients. The studies were conducted between 1997 and 2012, and the number of patients they investigated ranged from 40 to 227.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…The studies were conducted between 1997 and 2012, and the number of patients they investigated ranged from 40 to 227. Nine studies (Shiozaki et al, 2000;Hsu et al, 2008;Lin et al, 2008;Li et al, 2009;Nozoe et al, 2009;Situ et al, 2010;Chen et al, 2011;Wang et al, 2011;Lv et al, 2012) investigated patients with ESCC, and one (Krishnadath et al, 1997) investigated EAC. Although all the studies used immunohistochemical analysis to examine the expression of β-catenin, they made different criteria of β-catenin aberrant expression.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations